Housing Policies: The Experiences and Constraints of Housing Industry in Ghana - Ameh, Sunday Ojonugwa; Osafo, Benjamin Thomas (Advances in Social Sciences Research Journal, 2020)
Ghana housing policies in the pre- and post- independence have not been consistent and sustainable. Whiles the colonial government adopted self-help projects and piloted research findings, policies after independence focused on social housing, affordable housing and Public Private Partnership (PPP) projects. The impact of these policies did not improve the performance of the main stakeholders in the housing industry, thereby resulting to inadequate houses in most communities in Ghana. The research sought to identify the main challenges encountered by stakeholders in relation to government housing policies. The study adopted the exploratory and thematic literature review to ascertain the experiences and constraints faced by the Housing Industry (HI) in Ghana in relation to Ghana Housing Policies (GHP). The principle of demand and supply which determine the price mechanism in the housing market constitutes the theoretical orientation of the study. As such, challenges created by the housing policies in Ghana were related to the factors of demand and supply, principle of price mechanism and experiences of the global world and well as increase in urban shelter deviant rate. A comprehensive analysis was undertaken to reveal key findings on the challenges of the individual stakeholders namely households, financial institutions, estate developers and government land sector agencies. It was realized that prices of houses in Ghana were high in relation to households’ incomes. And that, the loan requirements of mortgage institutions of payment of 30% deposit, 50% monthly mortgage and 10 years mortgage term were unbearable by most households. It was recommended that estate developers should undertake demand assessment of households and the government should implement sustainable policies, hence reduce urban shelter deviant rate.